Selective debridement of burn wounds using hydrosurgery system. Issue 2 (29th November 2019) - Yuan, Mingzhou; Yin, Meifang; Zhang, Lijun; Feng, Jinghao; Zhu, Junyou; Zhou, Ziheng; Shu, Bin; Zhou, Fei; Zhang, Fangyingnan; Yin, Hanxiao; Wang, Xiaoyan; Qi, Shaohai; et al.
Abstract: In recent years, hydrosurgery is a technology that has been applied more and more in debridement procedures. However, the selectivity of hydrosurgery to cutaneous necrotic tissues has not been proved. This study was designed to investigate the possible tissue selectivity of hydrosurgery in the debridement in burn wounds. Deep partial‐thickness burns were produced on the back of porcine, and 48 hours later, both burn wounds and normal skin were debrided using the hydrosurgery system. Then tissue samples were taken, and histological staining was performed and observed under microscope. Burn wound resection rates and the normal skin damaged rates were measured. Our result indicated that the burn wounds were significantly more sensitive than the normal skin when the water pressure produced by the hydrosurgery system was set between 3000 and 5000 psi (pounds per square inch), that is, the necrotic tissue portions were debrided more easily than the normal skin tissue. Based on these data, we suggest that 3000 to 5000 psi of water pressure in the hydrosurgery system has a skin tissue selectivity in burn wounds.